Relationship between adjustment of low water level and utilization of water depth in Shashi Reach in middle Yangtze River - Fang, Juan-juan; Yang, Yun-ping; Jia, Meng-lin; Zhu, Yu-de; Wang, Jian-jun (Water Science and Engineering, 2022)
Hydrological, sediment, and bathymetric data of the Shashi Reach in the middle Yangtze River for the period of 1975–2018 were collected, and the characteristics of low water level changes and their impacts on utilization of water depth for navigation were investigated. The results showed that, during the study period, the Shashi Reach riverbed was significantly scoured and incised, with cross-sectional profiles showing overall narrowing and deepening. This indicated a strong potential to improve the water depth of the channel. The analysis of the temporal variation of in-channel topographical features showed that the Taipingkou diara underwent siltation and erosion, with its head gradually scoured and relocated downstream after 2008, and the Sanbatan diara continued to shrink and migrate leftwards. Low water levels with the same flow rate over the study period decreased. For instance, from 2003 to 2020, the water level at the Shashi hydrological station decreased to 1.37 m with a flow rate of 6 000 m3/s. Furthermore, the designed minimum navigable water level of the Shashi Reach was approximately 2.11 m lower than the recommended level. In terms of utilization of the channel water depth, continuous scouring of the river channel is expected to result in a reduction in discharge at the Taipingkou mouth, which will improve the water depth conditions of the channel during the dry season in the Shashi Reach. With several channel regulation projects, the 3.5-m depth of the Shashi Reach would basically be unobstructed. This promotes utilization of the shipping route from the Taipingkou south branch to the Sanbatan north branch as the main navigation channel during the dry season. Considering the factors of current water depth and the clear width limitation of the navigation hole at the Jingzhou Yangtze River Bridge, this route can still be favored as the main navigation channel with a 4.5-m depth during the dry season.